Preservation of fish male germplasm in Poland - Judycka, Sylwia; Dietrich, Mariola A.; Nynca, Joanna; Ciereszko, Andrzej (Frontiers in Marine Science, 2024)
The natural resources of a country, including ichthyofauna, constitute a vital aspect of its national heritage. Fish populations are threatened with loss of biodiversity as a result of human activity (anthropopressure), resulting in water pollution, habitat destruction and overfishing. Additionally, the escalating threat is exacerbated by climate change, primarily manifested in periodic reservoir and watercourse desiccation. Genetic variability of captive is also threated as fish raised in hatcheries are susceptible to bacterial and viral diseases. Therefore, methodologies for fish sperm cryopreservation aimed at safeguarding the gene pool of both natural and captive fish populations assume paramount importance for their conservation and mitigation of irreversible losses, particularly crucial in light of increasing ecological disasters. This paper offers an overview of cryopreservation research in Poland, tracing back to early initiatives in the 1970s concerning carp (Cyprinus carpio) semen and culminating in recent advancements, where standardized cryopreservation methodologies were developed. We delve into the freezing results of semen of various fish species, encompassing both wild specimens like whitefish (Coregonus lavaretus) and lake minnows (Eupallasella percnurus), and farmed species such as sturgeons, carp, and numerous salmonid species. Additionally, we delineate projects that support such endeavors. Recent milestones in the establishment of fish sperm cryobanks in Poland catering to both wild and farmed species, including carp and rainbow trout (Oncorhynchus mykiss)the most economically significant fish in Poland were presented. We also expound on the implementation of cryopreserved semen from sex-reversed rainbow trout in hatchery practices. Furthermore, we discuss significant challenges pertaining to sperm banking, particularly concerning funding and the practical utilization of cryostored semen samples for egg fertilization under hatchery conditions.